A Comment on "Review of Quasi-Analytical and Cavity Expansion Methods for Projectile Penetration of Concrete Targets", by R. Sobeski and G. Urgessa, Int. J. Protective Structures, 6(1), 43–64 (2015). Issue 3 (September 2015) - Rosenberg, Zvi; Dekel, Erez
The relevance of the cavity expansion analyses to the penetration mechanics of rigid projectiles, impacting metallic and concrete targets, is discussed. In the past six years we offered an alternative approach to that reviewed by Sobeski and Urgessa (2015), and we briefly discuss that work in this comment. To our best understanding, the cavity expansion analyses are irrelevant to the penetration mechanics of rigid projectiles impacting metallic or concrete targets.